2014
DOI: 10.1111/joms.12103
|View full text |Cite
|
Sign up to set email alerts
|

Harsh Evaluations of Entrepreneurs Who Fail: The Role of Sexual Orientation, Use of Environmentally Friendly Technologies, and Observers' Perspective Taking

Abstract: Although there is a pervasive anti‐failure bias in society, we investigate why some entrepreneurs who fail are evaluated more harshly than others. Building on attribution theory and the literatures on prejudice, pro‐social intentions, and perspective taking, we offer an evaluation model of entrepreneurial failure and test this model on 6,784 assessments made by 212 observers. We find that variance in the harshness of failure evaluations depends on both the attributes of the entrepreneur and the attributes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 156 publications
(228 reference statements)
1
50
0
7
Order By: Relevance
“…The higher a failure's financial costs, the higher the probability that others will notice the failure, often resulting in stigma for the individuals involved (Cardon et al 2011;Semadeni et al 2008;Sutton and Callahan 1987). For instance, our research (Shepherd and Patzelt 2015) showed that individuals with substantial financial losses as a result of failure are stigmatized more than those with lower losses. Stigma is a form of social stain as the individual being stigmatized experiences defamation that harms his or her reputation (see Cardon et al 2011;Shepherd and Patzelt 2015).…”
Section: Fear Motivating Entrepreneurial (In)actionmentioning
confidence: 63%
See 3 more Smart Citations
“…The higher a failure's financial costs, the higher the probability that others will notice the failure, often resulting in stigma for the individuals involved (Cardon et al 2011;Semadeni et al 2008;Sutton and Callahan 1987). For instance, our research (Shepherd and Patzelt 2015) showed that individuals with substantial financial losses as a result of failure are stigmatized more than those with lower losses. Stigma is a form of social stain as the individual being stigmatized experiences defamation that harms his or her reputation (see Cardon et al 2011;Shepherd and Patzelt 2015).…”
Section: Fear Motivating Entrepreneurial (In)actionmentioning
confidence: 63%
“…For instance, our research (Shepherd and Patzelt 2015) showed that individuals with substantial financial losses as a result of failure are stigmatized more than those with lower losses. Stigma is a form of social stain as the individual being stigmatized experiences defamation that harms his or her reputation (see Cardon et al 2011;Shepherd and Patzelt 2015). Ultimately, the social influence of stigmatized individuals diminishes significantly.…”
Section: Fear Motivating Entrepreneurial (In)actionmentioning
confidence: 98%
See 2 more Smart Citations
“…Beyond entrepreneurs' impressionmanagement strategies, do particular forms of failure and/or types of entrepreneurs cause greater stigma? For instance, Shepherd and Patzelt (2015) found that entrepreneurs who are homosexual are likely to be stigmatized more from business failure than those who are heterosexual (in one region of Germany) and that those who are trying to preserve the environment are stigmatized less for business failure than those who were not trying to preserve the environment. Perhaps female entrepreneurs in supposed "masculine" industries (or masculine organizations or roles) face more stigmatization from failure compared to women in "feminine" industries (or organizations or roles) or men in "masculine" industries (or organizations or roles).…”
Section: The Social Implications Of Entrepreneurial Failurementioning
confidence: 99%